Analisis Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal Open-Ended Ditinjau dari Gaya Kognitif - Oktaviana Putri, Anggita; Regina, Eka Putri (FKIP Universitas Mataram, 2025)
The research is a qualitative research with a descriptive approach. The data analysis techniques used in this research are test data analysis techniques and interview data analysis techniques. This study aims to analyze students' creative thinking abilities in solving open-ended problems viewed from their cognitive styles, namely reflective and impulsive. The research was conducted at MTs Ash-Shiddiqi Rejoyoso with 16 students participating. Data collection techniques included MFFT (Matching Familiar Figures Test) to determine cognitive styles and a creative thinking ability test on the topic of two-dimensional figures. two students were selected as research subjects: one reflective students categorized as